Porosity regrowth during heat treatment of hot isostatically pressed additively manufactured titanium components. (September 2016) - Tammas-Williams, S.; Withers, P.J.; Todd, I.; Prangnell, P.B.
Abstract: X-ray computed tomography has been used to track the behaviour of individual pores found in selective electron beam melted additive manufactured titanium. Porosity was found to shrink below the detection limit of X-ray microtomography (< 5 μm) upon hot isostatic pressing. Spherical argon containing gas pores, which have a high internal gas pressure following hot isostatic pressing, have been found to progressively reappear and grow in proportion to their original as-built size during high temperature (β-anneal) treatments, whereas larger irregular low pressure pores did not reappear. The implications of these observations in terms of additive manufacturing are discussed. Graphical abstract: